2020
DOI: 10.3390/plants9040502
|View full text |Cite
|
Sign up to set email alerts
|

Pathological, Morphological, Cytogenomic, Biochemical and Molecular Data Support the Distinction between Colletotrichum cigarro comb. et stat. nov. and Colletotrichum kahawae

Abstract: The genus Colletotrichum has witnessed tremendous variations over the years in the number of species recognized, ranging from 11 to several hundreds. Host-specific fungal species, once the rule, are now the exception, with polyphagous behavior regarded as normal in this genus. The species Colletotrichum kahawae was created to accommodate the pathogens that have the unique ability to infect green developing coffee berries causing the devastating Coffee Berry Disease in Africa, but its close phylogenetic relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 68 publications
(126 reference statements)
0
12
0
1
Order By: Relevance
“…According to our knowledge, this study is the first report of C. boninense , C. fructicola , and C. perseae affecting olive trees. Other studies have described another six Colletotrichum species associated with this crop, C. aenigma , C. cigarro , C. karstii , C. queenslandicum , C. lupini , and C. rhombiborme [ 4 , 5 , 23 , 77 , 78 ]. Although many other woody crops are affected by numerous species of Colletotrichum [ 21 , 54 , 79 , 80 ], the olive tree is one of the plant species affected by the most remarkable diversity of taxa of this fungal genus with 18 species.…”
Section: Discussionmentioning
confidence: 99%
“…According to our knowledge, this study is the first report of C. boninense , C. fructicola , and C. perseae affecting olive trees. Other studies have described another six Colletotrichum species associated with this crop, C. aenigma , C. cigarro , C. karstii , C. queenslandicum , C. lupini , and C. rhombiborme [ 4 , 5 , 23 , 77 , 78 ]. Although many other woody crops are affected by numerous species of Colletotrichum [ 21 , 54 , 79 , 80 ], the olive tree is one of the plant species affected by the most remarkable diversity of taxa of this fungal genus with 18 species.…”
Section: Discussionmentioning
confidence: 99%
“…kahawae and C . cigarro were adopted from the study conducted by Cabral et al [ 33 ]. Phylogenetic tree showed that present isolates were clustered together with C .…”
Section: Resultsmentioning
confidence: 99%
“…ciggaro (Weir et al ., 2012). However, both subspecies were recently classified to species level using a polyphasic approach (Cabral et al ., 2020). Another example is C .…”
Section: Discussionmentioning
confidence: 99%